Positive Language Education in The AI Era: Cultivating a Madani Generation in Malaysia - Fathima Rawshan; Suzanah Selamat; Fariza Puteh Behak; Sarifah Nurhanum Syed Sahuri; Mohamed Mihlar Abdul Muthaliff; Siti Nur Baiin Che Harun (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia